Penyembuhan Gangguan Mental dengan Terapi Shirodhara dalam Pengobatan Ayurveda - Ni Luh Putu Novita Rosana Lestari; Chieko Maeda (UHN IGB Sugriwa Denpasar, 2021)
The complexity of modern life leads humans to adapt to create a healthy life behind the hustle and bustle of the world. Globalization and various advanced technologies require humans to be able to adapt to existing technology. The existence of competition from various sectors and the inability of humans to control themselves are the main causes of mental disorders which ultimately affect physical health. Mental disorder is a disease that can hinder a person's success in achieving his goals. If the symptoms of mental disorders such as stress, anxiety, etc. continue to be ignored, it will result in the emergence of chronic mental disorders. Humans try to prevent and treat symptoms and mental illness by utilizing pharmacological drugs that are instant healing, but if consumed in the long term it can have negative effects on body health. The alternative given by ancient ayurvedic medicine in dealing with mental disorders is the Shirodhara terapi. This terapi is believed to be able to provide a sensation of calm to the patient, reduce stress, anxiety and various health problems related to mental disorders. The use of warm herbal oil in this terapi may have no side effects